Genetic Algorithm for optimisation of distribution system in a single stage supply chain network with fixed charges. (1st January 2011) - Manimaran, P.; Selladurai, V.; Ranganathan, Rajesh; Sasikumar, G.
This paper proposes a single stage supply chain network fixed charge transportation problem (FCTP) and a solution procedure. The objective is to find the optimum set of suppliers to be opened and determine the quantities to be supplied, so that the total cost of distribution can be minimised. The problem chosen goes beyond the traditional mathematical programming and it becomes a non-polynomial (NP) hard problem, particularly while considering the fixed charges. Genetic Algorithm (GA) approach is proposed in this paper for solving. GA is applied for optimisation of the distribution network to provide optimal or near optimal solution. To demonstrate the efficiency of the proposed method in FCTP, GA is compared with spanning tree-based GA with the aid of numerical examples. Following application and analysis of this methodology, the proposed method is identified to be efficient concerning the total distribution cost. Further, the accuracy and procedure of selecting the suitable suppliers for meeting the customer needs are found simple and systematic in approach.